Pluralisme Agama sebuah Keniscayaan - Taslim HM. Yasin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Ahlu al-Kitab has become one of the unique concepts in Islam. Islam acknow-ledges the holy books and the ummah prior to Islam. This acknowledgement does not means that all religions are the similar to all aspects. Since each religion has its distinct creeds, rituals and code of conducts, all religions are to respect and tolerate each other. Through respect and tolerance, all religions can cooperate and solve problems of religious, social, political and cultural issues emerging in their ummah. This is what calls religious pluralism concept that aims to built a harmonious and peaceful community, the community with pluralistic beliefs, but united to handle the problems of its people.